Panacea to lost gingival tissue architecture and spacing: Silicone gingival prosthesis - Brajendra S Tomar; G S Chandu; Shubhra Singh; Manish Goutam (Wolters Kluwer Medknow Publications, 2016)
The positive psychological effects of improving patients' smile often contribute to an improved self-image and enhanced self-esteem. Periodontal disease may lead to tooth and tissue loss that can result in esthetic problems. Combined periodontal/prosthodontic treatment for patients with advanced disease is well documented. This case report illustrates a method of treatment for an advanced tissue loss in an esthetic area using a removable silicone gingival prosthesis/mask.